(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
It is a fundamental requirement of the fair procedure that it must contain provisions for the review of Judgments, orders and sentences passed by the court.Until the enactment of the Criminal Appeal Act of 1907 (repealed) a modern and satisfactory system of Appellate review was not available. The constitution of India and the Cr.P.C. 1973 provide for a review of decision of lower court by appropriate AppellateProvisional authority.Accordingly Appeal denotes the right of carrying a particular case from an inferior to a superior court to ascertain whether the judgment is sustainable. An appeal is a peripheral of the statute and there is no inherent right of appeal.As per black’s law dictionary A proceeding assumed to have a decision re-examined by higher authority predominantly, the submission of a lower Court’s or agency’s decision to higher court for review and possible reversal.